Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.

Access to harmonine, a chemical weapon of ladybird beetles - Philkhana, Satish Chandra; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Reddy, D. Srinivasa (RSC Advances, 2014)
The synthesis of harmonine, a defense alkaloid from the harlequin ladybird is reported by three different routes. The preparation of several new analogs with the same molecular weight and the decoration of gold nanoparticles with harmonines are also part of the present communication.

First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine

Synthesis and biological evaluation of palmyrolide a macrocycles as sodium channel blockers towards neuroprotection - Philkhana, Satish Chandra; Mehrotra, Suneet; Murray, Thomas F.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2016)
Palmyrolide A is a neuroprotective macrolide isolated by Gerwick and coworkers in 2010. This natural product is known to suppress neuronal spontaneous calcium ion oscillations through its voltage-gated sodium channel blocking ability which is of significant interest in CNS drug discovery. Herein, we give a detailed account on total synthesis of (+)-palmyrolide A and synthesis of a focused library of macrocycles around the scaffold, followed by their biological evaluation. Use of the chiral pool approach, Zhu's oxidative homologation, access to unnatural cis-palmyrolide A, preparation of 18 new analogues and identification of macrolides with improved sodium channel blocking activity are the important features of the present paper. As a measure of potency as voltage-gated sodium channel blockers, all the synthesized analogues were profiled for their ability to inhibit the veratridine-stimulated Na+ influx in murine primary neuronal cultures. Four macrocycles were found to be more potent or comparable to that of the natural product (-)-palmyrolide A. The most potent compound from this series 20 was structurally simplified and readily accessible in good quantities for further biological profiling.

Identification of new anti-inflammatory agents based on nitrosporeusine natural products of marine origin - Philkhana, Satish Chandra; Verma, Abhishek Kumar; Jachak, Gorakhnath R.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2017)
Nitrosporeusines A and B are two recently isolated marine natural products with novel skeleton and exceptional biological profile. Interesting antiviral activity of nitrosporeusines and promising potential in curing various diseases, evident from positive data from various animal models, led us to investigate their anti-inflammatory potential. Accordingly, we planned and synthesized nitrosporeusines A and B in racemic as well as enantiopure forms. The natural product synthesis was followed by preparation of several analogues, and all the synthesized compounds were evaluated for in vitro and in vivo anti-inflammatory potential. Among them, compounds 25, 29 and 40 significantly reduced levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines. In addition, these compounds suppressed several pro-inflammatory mediators including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF -kappa B), and thereby can be emerged as potent anti-inflammatory compounds. Furthermore, all possible isomers of lead compound 25 were synthesized, characterized and profiled in same set of assays and found that one of the enantiomer (-)-25a was superior among them. (C) 2017 Elsevier Masson SAS. All rights reserved.

Total synthesis of natural fregenedadiol and its diacetate, rearranged labdanes with aromatized B ring - Philkhana, Satish Chandra; Reddy, D. Srinivasa (Tetrahedron Letters, 2017)
Labdane based natural products are most abundant and widely distributed in nature with many compounds exhibiting exceptional biological properties. Fregenedadiol is a bicyclic diterpene isolated from Halimium viscosum and represents a new carbon skeleton fregenedane with its B ring aromatized. Here, we report a total synthesis of this interesting natural product using one-pot Diels-Alder/aromatization sequence and selective hydrogenolysis as key steps. (C) 2017 Elsevier Ltd. All rights reserved.

Nitrosporeusine analogue ameliorates Chandipura virus induced inflammatory response in CNS via NF kappa b inactivation in microglia - Verma, Abhishek Kumar; Waghmare, Trushnal S.; Jachak, Gorakhnath R.; Philkhana, Satish Chandra; Reddy, D. Srinivasa; Basu, Anirban (PLOS Neglected Tropical Diseases, 2018)
Chandipura Virus (CHPV), a negative-stranded RNA virus belonging to the Rhabdoviridae family, has been previously reported to bring neuronal apoptosis by activating several factors leading to neurodegeneration. Following virus infection of the central nervous system, microglia, the ontogenetic and functional equivalents of macrophages in somatic tissues gets activated and starts secreting chemokines, thereby recruiting peripheral leukocytes into the brain parenchyma. In the present study, we have systemically examined the effect of CHPV on microglia and the activation of cellular signalling pathways leading to chemokine expression upon CHPV infection. Protein and mRNA expression profiles of chemokine genes revealed that CHPV infection strongly induces the expression of CXC chemokine ligand 10 (CXCL10) and CC chemokine ligand 5 (CCL5) in microglia. CHPV infection triggered the activation of signalling pathways mediated by mitogen-activated protein kinases, including p38, JNK 1 and 2, and nuclear factor kappa B (NF-kappaB). CHPV-induced expression of CXCL10 and CCL5 was achieved by the activation of p38 and NF-kappaB pathways. Considering the important role of inflammation in neurodegeneration, we have targeted NF-kappaB using a newly synthesised natural product nitrosporeusine analogue and showed incapability of microglial supernatant of inducing apoptosis in neurons after treatment.